Parasitism of the “Fuller’s rose weevil” Naupactus cervinus by Microctonus sp. in Argentin - Rodriguero, Marcela Silvina (2014)
We report the occurrence of an unidentified species of the wasp Microctonus Wesmael (Hymenoptera: Braconidae) parasitizing adults of the Fuller’s rose weevil Naupactus cervinus (Boheman) (Coleoptera: Curculionidae), a widespread pest of economically important crops included in the South American tribe Naupactini. Cytochrome c oxidase subunit I-based phylogenetic analysis indicates that the parasitoid is closely related to Microctonus hyperodae Loan. Their first instar larvae show slight morphological differences with this species. Superparasitism by first instar larvae occurred at low frequency. Some teratocytes were observed. Microctonus sp. and its host were infected with different strains of the reproductive parasite Wolbachia pipientis Hertig (Rickettsiales: Rickettsiaceae), although the bacterial lineage harbored by the wasp coincides with that infecting most parthenogenetic Naupactini. This multipartite association (weevil bearing both Wolbachia and Microctonus, and Microctonus bearing Wolbachia) opens challenging perspectives for future research on biological interactions and biological control.